Case Report: Cholestatic liver disease in the course of erythropoietic protoporphyria associated with renal hypodysplasia and atrial septal defect - Lipiński, Patryk; Lipniacka, Agnieszka; Klaudel-Dreszler, Maja; Ziółkowska, Lidia; Kostrzewa, Grażyna; Odnoczko, Edyta; Wasilewski, Robert; Płoski, Rafał; Tylki-Szymańska, Anna (Frontiers in Pediatrics, 2025)
Erythropoietic protoporphyria (EPP) is an autosomal recessive disorder of the heme biosynthesis pathway caused by pathogenic variants in FECH gene resulting in a decreased activity of ferrochelatase. Liver involvement is observed in 5%–20% of patients harbouring loss-of-function FECH variants and its manifestations are heterogeneous, ranging from mildly elevated liver transaminases, cholelithiasis to severe acute cholestatic hepatitis/liver failure. This paper presents the case of a Polish infant with EPP associated with two novel missense FECH variants accompanied by other congenital anomalies, namely atrial septal defect and renal hypodysplasia. Progressive cholestatic liver disease (with subsequent congestive heart failure) was observed in the course of EPP. Erytropoietic protoporphyria should be considered in patients with hepatosplenomegaly and cholestasis accompanied by skin damage. The natural history of liver disease in the course of EPP could be determined by other factors, like the co-existence of congenital anomalies.